Implementation of Three Characters Education Design to Improve the Quality Of Academic Civitas College - Achmat Mubarok (STAI Miftahul Ula Nganjuk, 2017)
The implementation of character education in college was conducted through three character education design bases: First, class-based character education, conducted with the relationship between lecturers as educators and students as learners in In the classroom. Secondly, the education of character culture based on college campus, which is in the form of interaction with all members of academic Civitas who support, improve and strengthen, and leadership as a figure of transparency in Perform its work in accordance with its duties and functions. Third, the application of character education based on campus community is done by collaborating and always listening to community aspirations through co-operative Education Program (University cooperation with entrepreneurs, education, and society), Through the student Activities program.